OBTAINING AND TESTING OF MG-CA-SR BIODEGRADABLE MATERIALS USED IN MEDICINE - Kamel Earar; Ion Ciucă; Cornel Munteanu; Norin Forna; Anton Knieling; Alina Calin; Gabriela Leata (Romanian Journal of Oral Rehabilitation)
Biodegradable magnesium (Mg), calcium (Ca), and strontium (Sr) alloys have garnered significant interest in regenerative medicine due to their unique mechanical properties, biocompatibility, and controlled degradation combination. These materials are particularly promising for temporary implants, such as orthopedic screws, plates, and cardiovascular stents, as they eliminate the need for secondary surgical removal and provide osteogenic benefits through the release of bioactive ions. Despite their potential, the clinical implementation of Mg-Ca-Sr alloys faces several challenges, including precise control of degradation rates to match tissue healing, optimization of biocompatibility to prevent inflammatory responses, and addressing the complexities of industrial production for consistent quality and performance. Future research directions focus on employing advanced technologies like nano-engineering and 3D printing to tailor the properties of these alloys for specific applications. Long-term in vivo studies are critical for understanding their behavior in biological environments while combining these alloys with ceramics or polymers could create hybrid materials with enhanced mechanical strength and degradation control. Additionally, artificial intelligence offers opportunities to optimize material design and predict clinical outcomes. Mg-Ca-Sr alloys are promising to transform the landscape of biodegradable implants, address current limitations, and improve patient outcomes through innovative materials and fabrication techniques.